Transparency, trust, and integrated assessment models: An ethical consideration for the Intergovernmental Panel on Climate Change. (8th October 2020) - Robertson, Simon
Abstract: Following the trenchant criticism of the Intergovernmental Panel on Climate Change (IPCC) Fifth Assessment Report concerning the lack of transparency in integrated assessment models (IAMs), much attention has been given to addressing this issue in the preparation of the Sixth Assessment Report (AR6). The issue of IAM transparency has been an ongoing concern for approximately two decades regarding the cloaking of value‐laden assumptions and output uncertainties. Due to the opaque nature of IAMs, the credibility of modeling results and the associated policy recommendations are patently limited, with policymakers inevitably having reservations as to the robustness of modeling outcomes given the deficit of information regarding the underlying assumptions. In an attempt to address the issue of a lack of transparency concerning IAM usage by the IPCC, a database containing the climate mitigation scenario ensemble which underpinned the Special Report on Global Warming of 1.5°C was made publicly available, the IAMC 1.5°C Scenario Explorer database. Despite this database, the omission of critical model input data and accompanying supporting documentation from its content fails to fulfill its raison d'être, that is to say, to ensure reproducibility and transparency. If the issue of IAM transparency is not fully addressed in the upcoming AR6 with respect to the provision of IAM input data, accompanied by supporting documentation, then the IPCC will have failed to meet its own declared commitment for this assessment cycle. This article is categorized under: Integrated Assessment of Climate Change > Integrated Assessment Modeling Abstract : Illustrated by Owen Li, PhD.